PENGARUH MODEL SNOWBALL THROWING TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Wahyuni; Saidang; Arif Efendi A.S (STKIP Subang, 2026)
Low student learning motivation in Sciences and Social Sciences (IPAS) subjects is a common problem in elementary schools. One cause is the dominance of teacher-centered teaching methods, which limit students' opportunities for active participation. This study aims to determine the impact of the snowball throwing learning paradigm on student learning motivation during IPAS lessons at UPT SDN 13 Pinrang. Forty fifth-grade students were divided into two groups: a control group (19 students) who received conventional teaching and an experimental group (21 students) who received the snowball throwing model treatment. This study used a non-equivalent control group design and a quantitative, quasi-experimental methodology. Data were collected through observation, questionnaires, and documentation. Descriptive statistics, an independent sample t-test, and n-gain analysis were then used for analysis. The results show that the experimental group's average learning motivation score rose from 53.14 (pretest) to 65.48 (posttest). Compared to the control group, which experienced an increase from 53.42 to 58.47, this number is larger. The snowball throwing model significantly influences students' learning motivation, according to the results of the independent sample t-test, with a significance value of 0.010 (p below 0.05). Furthermore, the n-gain analysis revealed that the experimental group had an effectiveness rate of 59.47% (referred to as “moderately effective”), while the control group only achieved 26.09% (referred to as “ineffective”). Thus, it can be emphasized that the snowball throwing learning strategy has a significant and effective influence on increasing students' learning motivation in the science subject.